2005
DOI: 10.1103/physrevb.71.064415
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties in manganite thin films

Abstract: The resistivity of thin $La_{0.7}A_{0.3}MnO_{3}$ films ($A=Ca, Sr$) is investigated in a wide temperature range. The comparison of the resistivities is made among films grown by different techniques and on several substrates allowing to analyze samples with different amounts of disorder. In the low-temperature nearly half-metallic ferromagnetic state the prominent contribution to the resistivity scales as $T^{\alpha}$ with $\alpha \simeq 2.5$ for intermediate strengths of disorder supporting the theoretical pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 51 publications
3
35
1
Order By: Relevance
“…8. In previous studies on composite perovskites [11,[27][28][29][30][31][32][33][34], the increase in MR values at low temperatures has been attributed to grain boundary effects introduced by the dopant. Although, the mechanism of the grain boundary induced MR is not yet clear, some models have been proposed.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…8. In previous studies on composite perovskites [11,[27][28][29][30][31][32][33][34], the increase in MR values at low temperatures has been attributed to grain boundary effects introduced by the dopant. Although, the mechanism of the grain boundary induced MR is not yet clear, some models have been proposed.…”
Section: Resultsmentioning
confidence: 98%
“…As mentioned above, ρ 0 represents the resistance contribution due to the grain boundary effect. In many studies, it has been concluded that the value of ρ 0 can be considered a measure of the effective disorder [31]. In this case the increase of ρ 0 with Ag can be interpreted as a higher value of Ag and results in poor crystallinity with a disordered grain boundary structure.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is worth mentioning that the measurements of temperature dependent resistivity (q(T)), performed in a 4-square contact geometry for the different LSMO films investigated typically show very low residual resistivity (q(10 K) % 0.1 Â 10 -6 Xm), confirming their high crystal quality. 28 The morphology of the samples was investigated by means of scanning probe microscopy, in particular by AFM and STM. The average roughness (RMS) of the samples was found in the range of few unit cells (u.c.)…”
Section: Structural Morphological and Transport Characterizationmentioning
confidence: 99%
“…Extensive studies have been carried out on thin films of La 1−x Sr x MnO 3 . [39][40][41][42][43][44][45][46][47][48][49][50][51][52] The effects of strainfilm-thickness-induced modifications in various physical properties, such as magnetotransport and magnetic properties, [44][45][46][47][48][49][50][51][52][53][54][55][56][57] magnetic anisotropy, 39,40 optical properties, 40,50 and conduction noise, 38 have been investigated. However, nearly all of the studies related to the effect of strain have focused on La 1−x Sr x MnO 3 with a doping level of x ϳ 0.3 in which the one electron ͑e g ͒ bandwidth is large.…”
Section: Introductionmentioning
confidence: 99%